The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/13554794.2011.654218
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal dementia in eight Chinese individuals

Abstract: Frontotemporal dementia (FTD) has rarely been reported in Chinese populations. There are many potential reasons for this, including possible hesitancy on the part of patients or families to bring FTD-related symptoms to medical attention. Here, we present data on eight Chinese individuals, all of whom met criteria for the behavioral variant of FTD or the semantic variant of primary progressive aphasia. These patients presented for neurological evaluation at a relatively advanced stage. The mean MMSE score at i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…In addition, bvFTD individuals had the lowest number of completed CANTAB IED stages and typical bvFTD symptoms, such as apathy, compulsive behavior, deficits in executive functioning, and abrupt mood changes [ 26 ]. Our findings are in good agreement with previously reported results on the early diagnosis of bvFTD in the Chinese population [ 35 , 85 ] and provide evidence supporting the use of NPTs targeting social cognition in the clinical diagnosis of bvFTD.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, bvFTD individuals had the lowest number of completed CANTAB IED stages and typical bvFTD symptoms, such as apathy, compulsive behavior, deficits in executive functioning, and abrupt mood changes [ 26 ]. Our findings are in good agreement with previously reported results on the early diagnosis of bvFTD in the Chinese population [ 35 , 85 ] and provide evidence supporting the use of NPTs targeting social cognition in the clinical diagnosis of bvFTD.…”
Section: Discussionsupporting
confidence: 93%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. 3,4,5,6,7,8,9,10,11,12,13,15,16,17,18,21,24,25,27,28,29,30,33,34,35,36,37,38,40,41,42,43,45,46,47,48,49,50,52,53,55,56,57,58,59,60,62,63,64,65,66,67,68,70,71,72,73,74,75,76,…”
Section: Primary Topic Summariesmentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. 4,5,10,12,16,24,26,27,28,29,30,32,33,35,37,39,41,42,44,50,55,56,59,60,63,68,70,71,73,74,75,77,83,85,88,89,91,96,98,104,106,109,111,113,114,120,121,124,128,134,135,137,138,139,140,141,142,143,147,148,153,158,...…”
Section: Primary Topic Summariesmentioning
confidence: 99%
“…Cognitive deficits and awareness of memory problems were present years prior to diagnosis or onset of dementia [66,93]. A study on frontotemporal dementia in Chinese Americans found that symptoms of the disease in this group were similar to those in Caucasians [94].…”
Section: Symptoms and Clinical Functioningmentioning
confidence: 99%
“…Five studies in our review examined symptoms and clinical functioning of ADRD, with four out of the five studies stemming from the HAAS dataset [27,66,85,93,94]. Stewart et al (2005) found that dementiaassociated weight loss began before the onset of the clinical symptoms and accelerated by the time of diagnosis [85].…”
Section: Symptoms and Clinical Functioningmentioning
confidence: 99%